Analisis Pengaruh Lingkungan Kerja, Disiplin Kerja, dan Motivasi Kerja Terhadap Kinerja Karyawan PT Indonesia Abadi Jaya - Ahmad Prayudi; Zega, Yamolala; Nasution, Isnirobit (Jurnal Sains dan Teknologi, 2023)
This study aims to determine the effect of Work Environment, Work Discipline, and Work Motivation on Employee Performance of PT. Indonesia Abadi Jaya. The population in this study was 98 employees of PT. Indonesia Abadi Jaya. Sampling in this study with a total sampling technique, where the entire population is the sample, which amounts to 98 employees. Research using a quantitative approach. The instrument used is a scale/questionnaire of Work Environment, Work Discipline, Work Motivation, and Employee Performance that has been valid and reliable. This research was analyzed with multiple regression analysis tests. The results showed that: (1) There is a simultaneous and significant influence between Work Environment, Work Discipline, and Work Motivation on Employee Performance with F count = 21.075> F table value = 2.70 with a significance value of 0.000 (p < 0.05) (2) There is a partial and significant influence between Work Environment on Employee Performance with T count = 3.425> T table = 1.98 with a significance value of 0. 000 (p < 0.05), (3) There is a partial and significant influence between Work Discipline on Employee Performance with a value of Thitung = 2.978> Ttabel = 1.98 with a significance value of 0.000 (p < 0.05), and (4) There is a partial and significant influence between Work Motivation on Employee Performance with a value of Thitung = 2.867> Ttabel = 1.98 with a significance value of 0.000 (p < 0.05).